2003
DOI: 10.1155/s1110724303209074
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Targeting in Cancer Gene Therapy

Abstract: Cancer gene therapy has been one of the most exciting areas of therapeutic research in the past decade. In this review, we discuss strategies to restrict transcription of transgenes to tumour cells. A range of promoters which are tissue-specific, tumour-specific, or inducible by exogenous agents are presented. Transcriptional targeting should prevent normal tissue toxicities associated with other cancer treatments, such as radiation and chemotherapy. In addition, the specificity of these strategies should prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 199 publications
0
105
0
Order By: Relevance
“…1 However, only a few promoter systems incorporating both these elements have been utilized. Most recently Wang et al 39 successfully used a synthetic construct using HREs upstream of the Egr-1 promoter to control expression of HSV-TK in A549 lung adenocarcinoma xenografts.…”
Section: Radiosensitization Using Targeted Inos Gene Therapy Ho Mccarmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, only a few promoter systems incorporating both these elements have been utilized. Most recently Wang et al 39 successfully used a synthetic construct using HREs upstream of the Egr-1 promoter to control expression of HSV-TK in A549 lung adenocarcinoma xenografts.…”
Section: Radiosensitization Using Targeted Inos Gene Therapy Ho Mccarmentioning
confidence: 99%
“…A vast array of therapeutic regimens has been reported where transgenes are driven by a range of tissue or tumour specific, or alternatively, externally inducible promoters to achieve spatial and temporal control of gene expression. 1,2 By far the most widely studied system utilizes radiation-inducible elements from the Early Growth Response (Egr-1) gene. Weichselbaum and co-workers 3,4 have had much success using the CArG elements of the Egr-1 gene, reporting transcriptional control with both radiation and chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that tissue-or tumor-specific promoters, which are highly expressed in the liver, colon, melanoma, prostate or breast cancer, are capable of directing therapeutic gene expression in the tumor cells. [1][2][3][4][5] However, this approach has limitations as many of these promoters are active only in specific tumor types and some of the tissue-specific promoters can lead to serious side effects due to expression of therapeutic genes in normal cells. 1,6,7 Recently, a family of inhibitor of apoptosis (IAP) proteins has been characterized and their roles in blocking apoptotic pathways and heightening resistance to therapeutic reagents have been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Since they bind to a specific cell surface receptor, envelope proteins are the primary determinants of the cell specificity or tropism of a retrovirus, though additional tissuespecificity can be garnered through the use of promoter or enhancer elements within the virus genome to direct transgene expression (Robson and Hirst, 2003;Romano, 2004). Pseudotyping, the packaging of vectors with any of a number of heterologous viral envelope proteins rather than the retroviral envelope, can offer the ability to change or extend cell tropism (Cronin et al, 2005).…”
Section: Retroviral Vectorsmentioning
confidence: 99%